2011
DOI: 10.1007/s00296-011-2300-5
|View full text |Cite
|
Sign up to set email alerts
|

Familial antiphospholipid syndrome presenting as bivessel arterial occlusion in a 17-year-old girl

Abstract: the best of our knowledge, never described in the literature before.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In 2013, Jelušić et al [4] reported a case of a 17-year-old girl with primary APS developing subacute signs of hand and leg ischemia caused by radial and popliteal artery occlusions associated with triple APL positivity. The mother of the girl presented just months later with symptoms of super cial thrombophlebitis and blood tests showed triple APL positivity with possible secondary APS related to evolving SLE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2013, Jelušić et al [4] reported a case of a 17-year-old girl with primary APS developing subacute signs of hand and leg ischemia caused by radial and popliteal artery occlusions associated with triple APL positivity. The mother of the girl presented just months later with symptoms of super cial thrombophlebitis and blood tests showed triple APL positivity with possible secondary APS related to evolving SLE.…”
Section: Discussionmentioning
confidence: 99%
“…The exact incidence and prevalence of APS in children is unknown; however, it seems that primary and secondary APS occur in children with similar frequency [3]. Familial APS is very rare and juvenile primary APS in siblings is extraordinarily rare [4,5].…”
Section: Introductionmentioning
confidence: 99%